Preparation method of composite photocatalyst SnO2 / W18O49 and in-situ test method of electron transport mechanism
By growing W18O49 nanowires on SnO2 nanofibers, the LSPR modified composite photocatalyst SnO2/W18O49 is formed, which solves the problem of insufficient light absorption capacity of existing photocatalysts in the visible and infrared light regions, and achieves a significant improvement in photocatalytic activity.
Patent Information
- Application Number
- CN202411509967.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-28
AI Technical Summary
The existing semiconductor photocatalysts have low efficiency when utilizing sunlight, especially in the visible and infrared light regions, which leads to limited photocatalytic efficiency.
By growing W18O49 nanowires on SnO2 nanofibers, the LSPR modified composite photocatalyst SnO2/W18O49 is formed, and the thermal electrons are injected into the conduction band of SnO2 by using the LSPR effect of plasma W18O49 to improve the photocatalytic activity.
The light absorption capacity of the composite photocatalyst in the visible and infrared light regions was significantly improved, and the hydrogen yield reached 2.79 times that of SnO2, proving the effectiveness of LSPR modification.
Smart Images

Figure CN119406401A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energy materials, and in particular to a composite photocatalyst SnO2 / W modified by localized surface plasmon resonance (LSPR) 18 O 49 The preparation method and the application of in situ irradiation XPS in mechanism research. Background Art
[0002] The global energy shortage and environmental pollution problems are becoming increasingly serious, which has attracted widespread attention from the society. In order to meet people's growing energy needs, it is particularly important to seek sustainable, clean and efficient new energy production methods. Solar-driven semiconductor photocatalytic decomposition of water and reduction of carbon dioxide to produce hydrogen and carbon-based chemical fuels is called "artificial photosynthesis", which is an effective way to solve the energy crisis and environmental pollution. However, due to its inherent shortcomings, such as serious photogenerated carrier recombination and insufficient utilization of the solar spectrum, the photocatalytic efficiency of single semiconductors is still relatively low. In order to improve the activity of semiconductor photocatalysts, researchers have proposed many modification methods, such as morphology design, heterostructure construction, co-catalyst loading, introduction of vacancies and doping, plasma-excited hot electron injection, etc. A single modification method has very limited effect on the performance of semiconductor photocatalysts, while multiple modifications can combine the advantages of different modification methods to jointly improve the activity of photocatalysts, which is the direction of future photocatalyst design.
[0003] In recent years, designing and constructing efficient photocatalysts, preparing solar fuels by decomposing water and reducing carbon dioxide, and directly converting inexhaustible solar energy into chemical energy are regarded as effective solutions to energy crisis and environmental pollution. Morphological design, heterostructure construction, catalyst loading, defect engineering and other means can effectively improve the efficiency of semiconductor photocatalysts, but due to the narrow wavelength range of available sunlight, this improvement is still relatively limited. Among the sunlight reaching the ground, ultraviolet light, visible light and infrared light account for about 5%, 45% and 50% respectively. How to effectively utilize sunlight in the visible and infrared regions should become a new focus of efficient photocatalyst design. The localized plasmon surface resonance (LSPR) effect can significantly enhance the light absorption ability of materials in the visible and infrared regions. The plasmas currently used in photocatalyst design are mainly precious metals such as gold and silver. They are expensive and difficult to obtain, making large-scale application unrealistic. Therefore, how to develop and utilize non-precious metal plasmas to enhance light absorption has become the focus of current photocatalyst design. At the same time, due to the different excitation behaviors of plasmas and conventional semiconductors at different wavelengths, the mechanism of enhancing photocatalytic activity is not clear. Therefore, it is difficult to find reliable and effective means to study the mechanism of plasma-modified photocatalysts in the current design of plasma photocatalysts. 18 O49 It is a common non-precious metal plasma with a large number of oxygen vacancies on its surface, which can serve as active sites for reactions and are therefore often used in the design of photocatalysts. Summary of the invention
[0004] The present invention provides a reliable and convenient in-situ test method for electron transport path, which is used to study the LSPR modified composite photocatalyst SnO2 / W 18 O 49 The transmission path of electrons in the plasma. 18 O 49 The addition of W greatly improves the light absorption capacity of the system in the visible and infrared regions. 18 O 49 Hot electrons excited by the LSPR effect can be injected into the conduction band of SnO2 to participate in the catalytic reaction and enhance the activity of the system. Due to the complex composition of this multi-component photocatalyst, the abundant number of interfaces inside the material, and the additional photoelectron injection brought by LSPR, the traditional mechanism research method cannot accurately describe the transmission path of electrons under normal circumstances and under LSPR excitation, which brings great difficulties to the mechanism research. Therefore, the present invention proposes to use the in-situ irradiation XPS method to study the transfer direction of photogenerated electrons under different wavelengths, and irradiate the material with 300nm ultraviolet light and 700nm near-infrared light respectively to study the transmission direction of electrons in the material under two conditions.
[0005] In order to achieve the above object, the present invention provides the following scheme:
[0006] A composite photocatalyst SnO2 / W 18 O 49 Preparation method: SnO2 nanofibers prepared by electrospinning are dispersed in anhydrous ethanol, and then tungsten hexachloride is added and magnetically stirred to form a yellow transparent solution. The solution is then transferred to a hydrothermal reactor for solvothermal reaction. After the solution is cooled to room temperature, it is centrifuged three times with deionized water and twice with anhydrous ethanol, and then vacuum dried to obtain SnO2 / W 18 O 49 Composite photocatalyst.
[0007] Nanofibers were prepared by electrospinning, with a polymer solution flow rate of 0.5-2.0 mL / h, a drum speed of 80-200 rpm, a voltage of 12-25 kV, and a receiving distance between a syringe and an electrospinning receiving drum of 8-20 cm. Environmental parameters were adjusted: ambient temperature of 20-28° C., ambient humidity of 40-60%, a precursor solution was injected into a syringe with a needle, a high voltage static of 20 kV was applied to the needle, and a grounded rotating roller was used to receive the fibers. The obtained nanofibers were dried in an electric blast drying oven at 60° C. for 12 h, and then placed in a muffle furnace at 2° C. min. -1 The heating rate was raised to 600℃ and then kept warm for 100min to obtain SnO2 nanofibers.
[0008] The prepared SnO2 nanofibers were dispersed in anhydrous ethanol and tungsten hexachloride at a ratio of 1:10 and magnetically stirred for 7 to 12 hours to form a yellow transparent solution. The solution was then transferred to a 100 mL Teflon-lined stainless steel high-pressure hydrothermal autoclave and heated to 150 to 200°C at a heating rate of 1 to 3°C / min in an electric blast drying oven. The temperature was kept for 10 to 15 hours. After the solution was cooled to room temperature, it was centrifuged three times with deionized water and twice with anhydrous ethanol. The solution was then placed in a 55-60°C vacuum drying oven and dried for 8 to 12 hours to obtain SnO2 / W 18 O 49 Composite photocatalyst.
[0009] The composite photocatalyst SnO2 / W obtained by the preparation method 18 O 49 The in-situ test method of the electron transport mechanism is as follows: first, prepare the sample to be tested on the sample stage. After the preparation is completed, place the sample stage in the instrument transition chamber for pre-vacuuming. After the vacuum reaches the test requirements, send the sample stage into the test chamber for testing. Use in-situ irradiation XPS technology to study the electron migration path at different wavelengths. Install a light source with a light-guiding optical fiber in the original state, and irradiate the light onto the sample in the test chamber through the equipment observation window.
[0010] The irradiation wavelengths of the light source are 300nm ultraviolet light and 700nm near-infrared light, respectively, to study the migration direction of photogenerated electrons under different environments.
[0011] During the pre-vacuuming process, turn off all light sources in the transition chamber and the test chamber to place the sample in a completely dark environment. After the pre-vacuuming is completed, the completely dark conditions are also maintained during the test. At this time, the test results are the data under dark conditions; 300nm ultraviolet light and 700nm near-infrared light are added, and the test results are the data under light conditions.
[0012] Three-dimensional hierarchical morphology and plasma W 18 O 49The loading of W greatly improves the light absorption capacity of the system in the visible light region and near infrared light region. 18 O 49 The free electrons near the Fermi level are excited by the LSPR effect to become hot electrons and injected into the SnO2 conduction band to decompose water and produce hydrogen. At the same time, the photogenerated electrons excited to the SnO2 conduction band by ultraviolet light flow to W driven by the built-in electric field of the type II heterojunction. 18 O 49 The electrons in the conduction band return to the vicinity of the Fermi level and then return to replenish free electrons. This cyclic self-consistent electron transfer mechanism greatly enhances the photocatalytic activity of the system.
[0013] According to the electron shielding effect, the change in outer electron density caused by the transmission of electrons between components is ultimately reflected in the binding energy of the test element. An increase in binding energy indicates an outflow of electrons, and vice versa.
[0014] The beneficial effects of the present invention are as follows:
[0015] The present invention provides a LSPR modified composite photocatalyst SnO2 / W 18 O 49 The in-situ mechanism research method adopts the in-situ irradiation XPS technology, and studies the migration direction of photogenerated electrons under 300nm ultraviolet light and 700nm near-infrared light according to the characteristics of the two materials. Therefore, the present invention proposes to prepare SnO2 nanofibers by in-situ electrospinning technology, and then grow W on them by solvothermal method. 18 O 49 Nanowires, prepared SnO2 / W 18 O 49 Composite photocatalyst. Due to the plasma W 18 O 49 The addition of W greatly improves the light absorption capacity of the system in the visible and infrared regions. 18 O 49 Hot electrons excited by the LSPR effect can be injected into the conduction band of SnO2 to participate in the catalytic reaction and improve the activity of the system. The reason for the increased activity was revealed using the in situ irradiation XPS method.
[0016] The present invention studies the LSPR modified composite photocatalyst SnO2 / W 18 O 49 The in-situ test method of electron transport mechanism uses in-situ irradiation XPS to study the migration direction of photogenerated electrons under 300nm ultraviolet light and 700nm near-infrared light, revealing the reason for the improvement of the activity of the composite photocatalyst. 18 O 49 The loading of W greatly improves the light absorption capacity of the system in the visible light region and near infrared light region.18 O 49 The free electrons near the Fermi level are excited by the LSPR effect to become hot electrons and injected into the SnO2 conduction band to decompose water and produce hydrogen. At the same time, the photogenerated electrons excited to the SnO2 conduction band by ultraviolet light flow to W driven by the built-in electric field of the type II heterojunction. 18 O 49 The electrons in the conduction band return to the vicinity of the Fermi level and then return to replenish free electrons. This cyclic self-consistent electron transfer mechanism greatly enhances the photocatalytic activity of the system.
[0017] The in-situ mechanism research method provided by the present invention has the following characteristics: (1) Compared with the ordinary XPS test method, the light-adding experimental method can better simulate the scene of the photocatalyst in actual use. (2) The traditional mechanism research method cannot accurately describe the transmission path of electrons under normal circumstances and under LSPR excitation, which brings great difficulties to the mechanism research, while the XPS test method can reflect the electron transmission direction according to the change of binding energy.
[0018] SnO2 nanofibers were prepared by electrospinning and then non-noble metal plasma W was grown on them by solvothermal method. 18 O 49 Nanowires were prepared to obtain LSPR-modified SnO2 / W with three-dimensional hierarchical morphology. 18 O 49 Composite photocatalyst. Compared with SnO2, the photocatalytic activity of the catalyst is significantly improved, and the hydrogen production is 2.79 times that of SnO2. This shows that the composite photocatalyst prepared by the present invention has excellent catalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 To prepare LSPR modified SnO2 / W 18 O 49 Composite photocatalysts and XRD patterns and UV-vis DRS patterns of different samples;
[0020] Figure 2 The LSPR modified composite photocatalyst SnO2 / W was prepared 18 O 49 The morphology diagram;
[0021] Figure 3 The LSPR modified composite photocatalyst SnO2 / W prepared in Example 1 18 O 49 Activity test results:
[0022] Figure 4 Schematic diagram of the in-situ irradiation XPS device;
[0023] Figure 5The figure shows the SnO2 / W prepared in Example 2 18 O 49 In situ irradiation XPS spectra of composite photocatalyst samples (a) SnO2 / W 18 O 49 High-resolution W 4f in situ irradiation XPS spectra of the composite photocatalyst under 300nm and 700nm monochromatic light, (b) Sn3d in situ irradiation XPS spectrum. DETAILED DESCRIPTION
[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] The invention discloses LSPR modified composite photocatalyst SnO2 / W 18 O 49 The composite photocatalyst can obtain SnO2 nanofibers formed by stacking nanoparticles through electrospinning and subsequent calcination. The fiber has a diameter of about 400nm and has a large number of pores and cracks, which can provide a large number of active sites. The prepared SnO2 / W 18 O 49 The composite photocatalyst grew a large amount of W on the outside of SnO2 nanofibers. 18 O 49 The diameter of the nanowires and fibers increased to about 450nm.
[0026] LSPR modified composite photocatalyst SnO2 / W disclosed in the present invention 18 O 49 The preparation method is applied to high-efficiency photocatalysts, and the improvement of semiconductor photocatalyst performance by LSPR modification is verified. The steps are as follows:
[0027] (1) Preparation of SnO2 nanofibers: SnO2 nanofibers are prepared by electrospinning. First, add polyvinyl pyrrolidone (PVP), tin dichloride, anhydrous ethanol and N,N-dimethylformamide (DMF) to the sample bottle and stir with a magnetic stirrer until a transparent and uniform precursor solution is formed. Select a suitable needle model, adjust the appropriate temperature, humidity and other environmental factors through the temperature and humidity control system, and set the appropriate rotation speed, injection speed, step rate and other parameter values, inject the spinning solution into the syringe, and use an electrospinning machine to obtain nanofibers by electrospinning. SnO2 nanofibers are then obtained by drying and high-temperature treatment;
[0028] (2) SnO2 / W 18 O 49 Preparation of composite photocatalyst: The SnO2 nanofibers prepared in step (1) were dispersed in anhydrous ethanol, and then tungsten hexachloride was added thereto and magnetically stirred until a yellow transparent solution was formed. The solution was then transferred to a hydrothermal reactor and subjected to a solvothermal reaction in an electric blast drying oven. After the solution was cooled to room temperature, it was centrifuged three times with deionized water and twice with anhydrous ethanol, and then vacuum dried to obtain SnO2 / W 18 O 49 Composite photocatalyst;
[0029] (3)SnO2 / W 18 O 49 Mechanistic study of composite photocatalysts: using in situ irradiation XPS technology to study the electron migration paths at different wavelengths.
[0030] In step (1), the stirring time is 7 to 12 hours, the drying temperature is 60°C, and the drying time is 12 hours. After mixing 1g of tin dichloride with 2 to 3g of polyvinyl pyrrolidone (PVP), a certain amount of anhydrous ethanol and N,N-dimethylformamide are added and stirred evenly. 18 O 49 prepared by the same method without adding SnO2 nanofibers during the solvothermal process.
[0031] In step (2), the prepared SnO2 nanofibers are dispersed in anhydrous ethanol and tungsten hexachloride at a ratio of 1:10 and magnetically stirred to form a yellow transparent solution. The solution is then transferred to a 100mL Teflon-lined stainless steel high-pressure hydrothermal autoclave, heated to 150-200°C at a heating rate of 1-3°C / min in an electric blast drying oven, and kept warm for 10-15h. After the solution is cooled to room temperature, it is centrifuged three times with deionized water and twice with anhydrous ethanol, and then placed in a 60°C vacuum drying oven to dry overnight to obtain SnO2 / W 18 O 49 Composite photocatalyst.
[0032] In step (3), the prepared SnO2 / W 18 O 49 The composite photocatalyst was pasted on the surface of the conductive adhesive and sent to the XPS instrument for in-situ irradiation test. The irradiation light sources were selected as ultraviolet light with a wavelength of 300nm and near-infrared light with a wavelength of 750nm, respectively, to study the difference in electron migration under normal conditions and when the LSPR phenomenon occurs.
[0033] The technical solution of the present invention is further described below in conjunction with specific embodiments:
[0034] Example 1
[0035] SnO2, W 18 O 49 LSPR modified composite photocatalyst SnO2 / W with a ratio of 1:4 18 O 49 The preparation and mechanism study of is as follows:
[0036] (1) Preparation of SnO2 nanofibers: SnO2 nanofibers were prepared by electrospinning. First, 1.2 g polyvinyl pyrrolidone (PVP), 0.45 g tin dichloride, 5.6 mL anhydrous ethanol and 4.6 mL N,N-dimethylformamide (DMF) were added to a sample bottle and stirred overnight with a magnetic stirrer until a transparent and uniform precursor solution was formed. The precursor solution was injected into a syringe with a needle, and nanofibers were obtained by electrospinning using an electrospinning machine. The temperature and humidity control parameters were set as follows: temperature 30 °C, humidity 20%, and other environmental factors. The electrospinning parameters were set as follows: a No. 21 needle was selected, the needle injection speed was 0.6 mL / h, the roller speed was 100 rpm, the voltage was 20 kV, and the receiving distance between the syringe and the electrospinning receiving roller was 1 2 cm; the precursor solution was injected into a syringe with a needle, a high voltage static of 20 kV was applied to the needle, and a grounded rotating roller was used to receive the fiber. The obtained nanofibers were dried in an electric hot air drying oven at 60 °C for 12 h and then placed in a muffle furnace at 2 °C min -1 The heating rate was raised to 600℃ and then kept at this temperature for 100min to obtain SnO2 nanofibers;
[0037] (2) SnO2 / W 18 O 49 Preparation of composite photocatalyst: 50 mg of SnO2 nanofibers prepared in step (1) above were dispersed in 30 mL of anhydrous ethanol, and then 200 mg of tungsten hexachloride was added thereto and magnetically stirred until a yellow transparent solution was formed. The solution was then transferred to a 100 mL Teflon-lined stainless steel high-pressure hydrothermal autoclave, heated to 180°C in an electric blast drying oven, and kept warm for 12 hours. After the solution was cooled to room temperature, it was centrifuged three times with deionized water and twice with anhydrous ethanol, and then dried overnight in a 60°C vacuum drying oven to obtain SnO2 / W 18 O 49 Composite photocatalyst. 18 O 49 prepared by the same method without adding SnO2 nanofibers during the solvothermal process;
[0038] (3)SnO2 / W 18 O 49 Mechanism study of composite photocatalyst: SnO2 / W prepared in step (2) above 18 O 49The composite photocatalyst is pasted on the surface of the conductive adhesive and then sent to the XPS instrument for in-situ irradiation test. The X-ray source target of the test instrument is an aluminum target with a power of 150W and a ray energy of 1496eV. The irradiation light source is a wavelength continuously adjustable strong light source, model PLS EM-150, which is introduced into the cabin from the irradiation device installed on the side of the equipment to irradiate the sample.
[0039] After the preparation is completed, the sample stage is placed in the instrument transition chamber for pre-vacuuming. After the vacuum reaches the test requirements, the sample stage is sent to the test chamber for testing. In-situ irradiation XPS technology is used to study the electron migration path at different wavelengths. A light source with a light-guiding optical fiber is installed in the original state, and light is irradiated onto the sample in the test chamber through the equipment observation window. During the pre-vacuuming process, all light sources in the transition chamber and the test chamber are turned off to place the sample in a completely dark environment. After the pre-vacuuming is completed, the test process also maintains a completely dark condition. At this time, the test results are data under dark conditions; 300nm ultraviolet light and 700nm near-infrared light are added, and the test results are data under light conditions.
[0040] Figure 1 The LSPR-modified SnO2 / W prepared in this example 18 O 49 Composite photocatalyst (a) phase structure diagram, (b) UV-visible diffuse reflectance spectrum diagram. As can be seen from Figure (a), the prepared W 18 O 49 Nanowires and monoclinic W 18 O 49 The prepared SnO2 nanofibers are consistent with the standard card (JCPDS: 05-0392), and the prepared SnO2 / W 18 O 49 The composite photocatalyst has both monoclinic W 18 O 49 and tetragonal SnO2, proving the successful synthesis of the composite material. 18 O 49 The intrinsic absorption cutoff edge is about 410nm, indicating its semiconductor characteristics. 18 O 49 It also has a very wide absorption band from 450nm to the near-infrared region, reaching an absorption peak at around 1300nm. 18 O 49 The SPR effect similar to that of precious metals is caused by the collective resonance of a large number of electrons on the surface. Compared with pure SnO2, the composite photocatalyst SnO2 / W 18 O 49The absorption curve after 450nm shows an obvious upward curve, which proves that the plasma W 18 O 49 The successful loading of nanowires significantly enhanced the light absorption ability of SnO2 in the visible light region.
[0041] Figure 2 The LSPR modified composite photocatalyst SnO2 / W prepared in Example 1 18 O 49 SEM images of SnO2 nanofibers; Figure (b) shows that SnO2 nanofibers formed by stacking nanoparticles can be obtained by electrospinning and subsequent calcination. The diameter of the fiber is about 400nm, with a large number of pores and cracks, which can provide a large number of active sites. W as shown in Figure (c) can be prepared by solvothermal method. 18 O 49 Nanowires, without adding any template, will spontaneously cluster into a daisy-like shape, exposing the active sites on them. As can be seen in Figure (d), a large amount of W has grown outside the SnO2 nanofibers. 18 O 49 The diameter of the nanowires and fibers increased to about 450nm.
[0042] Figure 3 The (a) and (b) obtained in Example 1 are W 18 O 49 , SnO2 and SnO2 / W 18 O 49 The hydrogen production and average hydrogen yield changing with illumination time. Because the conduction band position cannot meet the potential required for hydrogen evolution reaction, W 18 O 49 It does not have photocatalytic hydrogen production activity
[90] The photocatalytic hydrogen production activity of SnO2 itself is also low. On the one hand, it is because the band gap of SnO2 is very wide, which makes it unable to utilize light in the visible light region and near-infrared light region. On the other hand, it is because there is a serious recombination phenomenon of photogenerated carriers inside SnO2. 18 O 49 The addition of SnO2 greatly enhances the light absorption capacity of SnO2 in the visible light region and near-infrared light region. 18 O 49 The hydrogen yield of the composite photocatalyst was significantly improved, which was 2.79 times that of SnO2.
[0043] Figure 4 Schematic diagram of the in-situ irradiation XPS device, SnO2 / W 18 O 49The composite photocatalyst is fixed on the surface of the sample stage by conductive glue. X-rays irradiate the sample to excite photoelectrons to escape from the material surface. After passing through the upper lens group and entering the hemispherical analyzer, the corresponding image is automatically drawn on the software according to the size of its kinetic energy. 300nm ultraviolet light and 750nm near-infrared light are introduced through the irradiation light source.
[0044] Figure 5 is the in-situ irradiation XPS spectrum, (ab) are SnO2 / W 18 O 49 ISI-XPS peak spectra of W 4f and Sn 3d of the composite photocatalyst under 700nm monochromatic light (top), without external light source (middle) and 300nm monochromatic light (bottom). Compared with the case without light, SnO2 / W under 300nm monochromatic light 18 O 49 The W 4f peak of SnO2 moves toward the direction of lower binding energy, while the Sn3d peak moves toward the direction of higher binding energy, indicating that under the external excitation light source of 300 nm, the photogenerated electrons are transferred from SnO2 to W 18 O 49 The wavelength of 300nm light source is between SnO2 and W 18 O 49 Intrinsic excitation band, at this wavelength, the electrons in the SnO2 valence band are excited to jump to its conduction band, and then flow to W driven by the built-in electric field. 18 O 49 The formation of type II heterojunction and the existence of built-in electric field can effectively realize the spatial separation of photogenerated carriers. 18 O 49 The conduction band potential is not enough to meet the occurrence of hydrogen evolution reaction, and no hydrogen will be produced in the system. Compared with the case without light, under 700nm monochromatic light, SnO2 / W 18 O 49 The W 4f peak of Sn 3d moves toward the direction of higher binding energy, while the W 4f peak of Sn 3d moves toward the direction of lower binding energy, indicating that the photogenerated electrons move from W 18 O 49 Flowing to SnO2. The light source with a wavelength of 700nm is located at W 18 O 49 The SPR band at this wavelength, the electrons in the SnO2 conduction band cannot be excited, due to the existence of the LSPR effect, W 18 O 49 The electrons near the Fermi level will be excited to generate hot electrons, which will then be injected into the conduction band of SnO2 to cause hydrogen evolution reaction. The above wavelength-dependent in-situ irradiation XPS test results strongly confirm that SnO2 / W 18 O 49 The composite photocatalyst has enhanced photocatalytic activity via hot electron injection.
[0045] Example 2
[0046] Preparation of SnO2, W 18 O 49 SnO2 / W composite photocatalyst with a three-dimensional hierarchical ratio of 1:6 18 O 49 Composite photocatalyst, the steps are as follows:
[0047] (1) Preparation of SnO2 nanofibers: SnO2 nanofibers were prepared by electrospinning. First, 1.2 g polyvinyl pyrrolidone (PVP), 0.45 g tin dichloride, 5.6 mL anhydrous ethanol and 4.6 mL N, N-dimethylformamide (DMF) were added to the sample bottle and stirred overnight with a magnetic stirrer until a transparent and uniform precursor solution was formed. The precursor solution was injected into a syringe with a needle, and the nanofibers were obtained by electrospinning using an electrospinning machine. The temperature and humidity control parameters were set as follows: temperature 30 °C, humidity 20%, and other environmental factors. The electrospinning parameters were set as follows: a No. 21 needle was selected, the needle injection speed was 0.6 mL / h, the roller speed was 100 rpm, the voltage was 20 kV, and the receiving distance between the syringe and the electrospinning receiving roller was 12 cm; the precursor solution was injected into a syringe with a needle, a high voltage static of 20 kV was applied to the needle, and a grounded rotating roller was used to receive the fiber. The obtained nanofibers were dried in an electric hot air drying oven at 60 °C for 12 h and then placed in a muffle furnace at 2 °C min -1 The heating rate was raised to 600℃ and then kept at this temperature for 100min to obtain SnO2 nanofibers;
[0048] (2) SnO2 / W 18 O 49 Preparation of composite photocatalyst: Disperse 50 mg of SnO2 nanofibers prepared in step (1) above in 30 mL of anhydrous ethanol, then add 300 mg of tungsten hexachloride and stir magnetically until a yellow transparent solution is formed. Then transfer the solution to a 100 mL Teflon-lined stainless steel high-pressure hydrothermal autoclave, heat it to 180°C in an electric blast drying oven and keep it warm for 12 hours. After the solution is cooled to room temperature, centrifuge it three times with deionized water and twice with anhydrous ethanol, and then dry it in a 60°C vacuum drying oven overnight to obtain SnO2 / W 18 O 49 Composite photocatalyst. 18 O 49 prepared by the same method without adding SnO2 nanofibers during the solvothermal process.
[0049] Example 3
[0050] Preparation of SnO2, W 18 O49 SnO2 / W composite photocatalyst with a three-dimensional hierarchical ratio of 1:8 18 O 49 Composite photocatalyst, the steps are as follows:
[0051] (1) Preparation of SnO2 nanofibers: SnO2 nanofibers were prepared by electrospinning. First, 1.2 g polyvinyl pyrrolidone (PVP), 0.45 g tin dichloride, 5.6 mL anhydrous ethanol and 4.6 mL N,N-dimethylformamide (DMF) were added to a sample bottle and stirred overnight with a magnetic stirrer until a transparent and uniform precursor solution was formed. The precursor solution was injected into a syringe with a needle, and nanofibers were obtained by electrospinning using an electrospinning machine. The temperature and humidity control parameters were set as follows: temperature 30 °C, humidity 20%, and other environmental factors. The electrospinning parameters were set as follows: a No. 21 needle was selected, the needle injection speed was 0.6 mL / h, the roller speed was 100 rpm, the voltage was 20 kV, and the receiving distance between the syringe and the electrospinning receiving roller was 12 cm; the precursor solution was injected into a syringe with a needle, a high voltage static of 20 kV was applied to the needle, and a grounded rotating roller was used to receive the fiber. The obtained nanofibers were dried in an electric hot air drying oven at 60 °C for 12 h and then placed in a muffle furnace at 2 °C min -1 The heating rate was raised to 600℃ and then kept at this temperature for 100min to obtain SnO2 nanofibers;
[0052] (2) SnO2 / W 18 O 49 Preparation of composite photocatalyst: Disperse 50 mg of SnO2 nanofibers prepared in step (1) above in 30 mL of anhydrous ethanol, then add 400 mg of tungsten hexachloride and stir magnetically until a yellow transparent solution is formed. Then transfer the solution to a 100 mL Teflon-lined stainless steel high-pressure hydrothermal autoclave, heat it to 180°C in an electric blast drying oven and keep it warm for 12 hours. After the solution is cooled to room temperature, centrifuge it three times with deionized water and twice with anhydrous ethanol, and then dry it in a 60°C vacuum drying oven overnight to obtain SnO2 / W 18 O 49 Composite photocatalyst. 18 O 49 prepared by the same method without adding SnO2 nanofibers during the solvothermal process.
[0053] The above is the LSPR modified SnO2 / W provided by the present invention 18 O 49The composite photocatalyst and its preparation method are introduced in detail. Specific examples are used in this article to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, several improvements and modifications can be made to the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A composite photocatalyst SnO2 / W 18 O 49 The preparation method is characterized in that: The SnO2 nanofibers prepared by electrospinning were dispersed in anhydrous ethanol, and tungsten hexachloride was added and magnetically stirred to form a yellow transparent solution. The solution was then transferred to a hydrothermal reactor for solvothermal reaction. After the solution was cooled to room temperature, it was centrifuged three times with deionized water and twice with anhydrous ethanol, and then vacuum dried to obtain SnO2 / W 18 O 49 Composite photocatalyst.
2. The composite photocatalyst SnO2 / W according to claim 1 18 O 49 The preparation method is characterized in that: Nanofibers were prepared by electrospinning. The flow rate of the polymer solution was 0.5-2.0 mL / h, the drum speed was 80-200 rpm, the voltage was 12-25 kV, and the receiving distance between the syringe and the electrospinning receiving drum was 8-20 cm. The environmental parameters were adjusted as follows: the ambient temperature was 20-28 °C, the ambient humidity was 40-60%, the precursor solution was injected into a syringe with a needle, a high voltage static of 20 kV was applied to the needle, and a grounded rotating roller was used to receive the fiber. The obtained nanofibers were dried in an electric blast drying oven at 60 °C for 12 h, and then placed in a muffle furnace at 2 °C·min -1 The heating rate was increased to 600 ℃ and then kept warm for 100 min to obtain SnO2 nanofibers.
3. The composite photocatalyst SnO2 / W according to claim 1 18 O 49 The preparation method is characterized in that: The prepared SnO2 nanofibers were dispersed in anhydrous ethanol and tungsten hexachloride at a ratio of 1:10 and magnetically stirred for 7-12 h to form a yellow transparent solution. The solution was then transferred to a 100 mL Teflon-lined stainless steel high-pressure hydrothermal autoclave and heated to 150-200 °C at a heating rate of 1-3 °C / min in an electric blast drying oven. The temperature was kept at this temperature for 10-15 h. After the solution was cooled to room temperature, it was centrifuged three times with deionized water and twice with anhydrous ethanol. The solution was then placed in a 55-60 °C vacuum drying oven and dried for 8-12 h to obtain SnO2 / W 18 O 49 Composite photocatalyst.
4. The composite photocatalyst SnO2 / W obtained by the preparation method of claim 1 18 O 49 An in-situ test method for the electron transport mechanism, characterized in that: First, prepare the SnO2 / W to be tested on the sample stage 18 O 49 After the composite photocatalyst sample is prepared, the sample stage is placed in the instrument transition chamber for pre-vacuuming. After the vacuum reaches the test requirements, the sample stage is sent into the test chamber for testing. The in-situ irradiation XPS technology is used to study the electron migration path at different wavelengths. A light source with a light-guiding optical fiber is installed in the original state, and light is irradiated onto the sample in the test chamber through the equipment observation window.
5. The composite photocatalyst SnO2 / W according to claim 4 18 O 49 An in-situ test method for the electron transport mechanism, characterized in that: The irradiation wavelengths of the light source are 300 nm ultraviolet light and 700 nm near-infrared light.
6. The composite photocatalyst SnO2 / W according to claim 1 or claim 4 18 O 49 An in-situ test method for the electron transport mechanism, characterized in that: During the pre-vacuuming process, turn off all light sources in the transition chamber and the test chamber to place the sample in a completely dark environment. After the pre-vacuuming is completed, the completely dark conditions are also maintained during the test. At this time, the test results are the data under dark conditions; 300 nm ultraviolet light and 700 nm near-infrared light are added, and the test results are the data under light conditions.
Citation Information
Patent Citations
Nanocrystalline metal oxide with p-n composite structure, preparation method and application of nanocrystalline metal oxide
CN103966697A
Preparation method of plasma-treated nano-fiber hydrogen sensing material
CN111349974A